Canadian Association of Radiologists/Canadian Association for Interventional Radiology/Canadian Society of Thoracic Radiology Guidelines on Thoracic Interventions. Issue 2 (May 2023) - Nguyen, Elsie T.; Bayanati, Hamid; Hurrell, Casey; Aitken, Matthew; Cheung, Edward M.; Gupta, Ashish; Harris, Scott; Sedlic, Tony; Taylor, Jana Lyn; Gahide, Gerald; Dennie, Carole
Thoracic interventions are frequently performed by radiologists, but guidelines on appropriateness criteria and technical considerations to ensure patient safety regarding such interventions is lacking. These guidelines, developed by the Canadian Association of Radiologists, Canadian Association for Interventional Radiology and Canadian Society of Thoracic Radiology focus on the interventions commonly performed by thoracic radiologists. They provide evidence-based recommendations and expert consensus informed best practices for patient preparation; biopsies of the lung, mediastinum, pleura and chest wall; thoracentesis; pre-operative lung nodule localization; and potential complications and their management.